Fairness- and cost-effectiveness-based approaches to effort-sharing under the Paris agreement - Jakob Wachsmuth; Alexandra Denishchenkova; Hanna Fekete; Paola Parra; Michiel Schaeffer; Andrzej Ancygier; Fabio Sferra (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2019)
The current nationally determined contributions of the Parties to the Paris Agree-ment are far from being sufficient to achieve the long-term goal to limit global warming. Therefore, the question of how to distribute the global mitigation burden among the Parties in a fair and cost-effective way remains topical. In this paper, approaches based on different fairness criteria and the criterion of cost-effective-ness are applied to a global emission budget compatible with the Paris targets and evaluated for the globally largest emitters including the EU as well as Ger-many. The results show that domestic mitigation efforts need to be increased in the majority of those countries even more than for the below-2êC limit of the Can-cun Agreements. Moreover, even if the cost-effective level is assumed to be reached, there remains a strong need for support by the historical large emitters to others from a fairness perspective. – – Die derzeitigen national festgelegten Beiträge der Vertragsparteien des Pariser Abkommens reichen bei weitem nicht aus, um das langfristige Ziel zur Begren-zung der Erderwärmung zu erreichen. Daher bleibt die Frage, wie die globale Minderungslast auf faire und kostengünstige Weise auf die Vertragsparteien ver-teilt werden kann, aktuell. In diesem Beitrag werden Ansätze, die auf unterschied-lichen Fairnesskriterien und dem Kriterium der Kosteneffizienz basieren, auf ein globales Emissionsbudget angewendet, das mit den Pariser Zielen vereinbar ist, und für die weltweit größten Emittenten einschließlich der EU und Deutschlands ausgewertet. Die Ergebnisse zeigen, dass die inländischen Minderungsmaßnah-men in den meisten dieser Länder noch mehr verstärkt werden müssen als für die in den Cancun-Abkommen festgelegten Grenze von unter 2êC. Selbst wenn davon ausgegangen wird, dass das kosteneffektive Niveau erreicht wird, besteht aus einer Fairnessperspektive darüber hinaus ein großer Bedarf an Unterstüt-zung durch die historischen Großemittenten ggü anderen.
urn:nbn:de:0011-n-5461729; Additional information: Im Rahmen des UFOPLAN-Vorhabens "Implikationen des Pariser Klimaschutzabkommens auf nationale Klimaschutzanstrengungen".
Keywords: 330